SYSTEM OF THE AUTOMATED CHECKING OLYMPIC SOLUTIONS UNIVERSAL OLYMP CHECKER V.1.1. - Alekseichuk, I.B. (Journal of Information Technologies in Education (ITE), 2009)
Article is devoted a problem of creation of system of the automated testing olympiad problems. The overall objective of the given report – to share experience in working out and introduction of software for automatic checking.